Integrating National Digital Identity to Prevent Minors’ Transactions on the Roblox Platform - Veren Widjaja; Alisya Lidya Rahma; Riyanto, Tio (JURNAL USM LAW REVIEW, 2025)
This study examines the effectiveness of age verification mechanisms on the Roblox platform and proposes the integration of Indonesia’s national digital identity system—specifically the Electronic Identity Card (e-KTP) and Digital Population Identity (IKD)—to prevent unauthorized digital transactions by minors. The research is motivated by the increasing vulnerability of children to financial exploitation through virtual currency purchases and the misalignment between global platform governance and Indonesia’s legal standards on legal capacity, parental consent, and personal data protection. Employing a normative juridical method with statutory, conceptual, and comparative approaches, this study analyzes Indonesian regulations on child protection, civil capacity, and data privacy alongside global age verification practices. The findings reveal that existing verification methods, which rely on self-declared data, document uploads, or biometric systems, are easily manipulated, legally insufficient, and pose significant data protection risks, particularly in cross-border data processing. In contrast, an e-KTP/IKD-based verification model using a binary “Yes/No” eligibility response offers a legally compliant, privacy-preserving, and preventive solution that aligns with Indonesia’s Civil Code, Child Protection Law, and Personal Data Protection Law, while remaining compatible with international standards such as COPPA and GDPR. The novelty of this study lies in proposing a state-verified digital identity integration model that bridges national legal frameworks with global digital platforms to ensure verifiable parental consent and protect minors from economic exploitation. This model contributes to the development of secure, accountable, and child-centered digital governance in Indonesia’s evolving digital economy.